Women's Empowerment Strategy Through Working Groups (POKJA) in Sidoagung Village - Boan Tua Utama Siregar; Zulkifli Lubis; Warjio Warjio (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2026)
Food sovereignty has become an important issue amid the increasing dependence on external food supplies and the declining attention to local food consumption in urban areas. In Medan City, this condition has encouraged the emergence of the Sumatran Youth Food Movement (SYFM), a youth-based community that advocates local food sovereignty through collective action and public awareness campaigns. This study aims to analyze the food conditions that underlie the emergence of SYFM, examine its characteristics as a New Social Movement, and describe the strategies employed in promoting local food sovereignty. The research uses a qualitative descriptive approach. Data were collected through in-depth interviews with key informants involved in the movement, supported by documentation and literature studies. The findings reveal that SYFM emerged as a response to food dependency, the dominance of imported food products, and the declining appreciation of local food among urban communities. As a New Social Movement, SYFM is characterized by its food sovereignty ideology, youth and student-based participation, participatory organizational structure, and the use of educational campaigns, public actions, and alternative economic practices. Through discussions, socialization programs, local food campaigns, and collaboration with local farmer cooperatives, SYFM contributes to increasing public awareness of local food, encouraging changes in consumption behavior, and strengthening support for local agricultural products. The study concludes that local food sovereignty can be promoted not only through government policies but also through community-based youth movements that foster social awareness and collective action at the local level.